The Role of Graduates of Arabian Universities in the Development of Maqasid al-Shari’ah in Nigeria - Mukhtar Umar Dagimun (Transpublika Publisher, 2025)
The science of Maqasid al-Shari’ah did not emerge until in the 4th century, however its concept is rooted in the Qur’an and Sunnah of the Prophet (SAW). It is based on wisdom and achieving people’s welfare. It is very essential in solving the numerous problems of the society particularly in the modern age. This paper examines the contribution of graduates of Arabian Universities to the advancement of the science of Maqasid al-Shari’ah in Nigiera. The main objective of this paper is to show how these graduates through their different programs assist in the development of the science which was mostly unknown to many people. The major finding of this paper revealed that though majority of these scholars do not take the science as a specialization, they however help in organizing lectures and Daurah on the science at various places in the country. This particularly helped in the spread and development of Maqasid al-Shari’ah in Nigeria. In writing this paper, both qualitative and library methods were adopted. In Qualitative method, oral interview was used to gather relevant data from the relevant stakeholders. In addition to interview, relevant library materials, theoretical works, audios and videos on Maqasid al-Shari’ah were also consulted and utilized.